دراسة كيميائية وبيولوجية لمستخلصات بذور السمسم الخام ) Sesamum indicum - حمامه, فاطمة الزهرة; قرفي, رانية (university of eloued جامعة الوادي, 2023)
يهدف عملنا إلى دراسة المستخلصات الخام لبذور السمسم ) Sesamum indicum ( من خلال الكشف الأولي للمواد الفعالة ا ولتقدير الكمي للفينولات والفلافونيدات ودراسة الفعالية المضادة للأكسدة وذلك بإجراء اختبارين (DPPH-CAT) ، والتي تمت مقارنتها بالنتائج المتحصل عليها مع دراسات سابقة . أما فيما يخص القدرة الفعالية المضادة للبكتيريا والفطريات فكانت النتائج سلبية مع كامل الأنواع. من جهة أخرى، ومن أجل تحديد جودة ونقاوة المستخلص الزيتي أُجْريت اختبارات فيزيوكيميائية حددنا من خلالها المؤشرات التالية:  الكثافة النسبية.  مؤشر الانكسار.  الامتزاجية في الإيثانول.  رقم الحموضة.  رقم البيروكسيد. المستخلص الذي أعطى لنا أفضل النتائج في كل هذه الاختبارات والتقديرات كانت للمستخلص المحمص وهذا راجع للثبات التأكسدي الحاصل.Our work aims to study the crude extracts of sesame seeds (Sesamum indicum) through the initial detection of the active substances and the quantitative determination of phenols and flavonoids and the study of the antioxidant activity by conducting two tests (DPPH-CAT), which were compared with the results obtained with previous studies. As for the anti-bacterial and anti-fungal efficacy, the results were negative with all species. On the other hand, in order to determine the quality and purity of the oil extract, physiochemical tests were conducted, through which we identified the following indicators:  Relative density.  Refractive index.  Miscibility in ethanol.  Acidity number.  Peroxide number. The extract that gave us the best results in all these tests and estimates was for the roasted extract, and this is due to the oxidative stability obtained.
مذكرة ماستر كيمياء
Keywords: لكلمات المفتاحية: بذور السمسم، Sesamum indicum ، المركبات الفينولية، DPPH ، TAC ، الفعالية المضادة للبكتيريا.; sesame seeds, Sesamum indicum, phenolic compounds, DPPH, TAC, antibacterial activity.